DYNAMICAL FRICTION IN THE LOCAL GROUP - Kudinova, A. V. (Одеські астрономічні публікації, 2013)
In this paper we consider dynamical behavior of the astrophysical objects in the Local Group. The motion of Andromed and The Milky Way is studied. We distinguish two different models: for the first one we do not take into account the influence of the Intra-Group Matter (IGrM), for the second one we take into account the dynamical friction due to the IGrM. We obtained some characteristic IGrM parametres such as particle masses for principle cases of the collision between the giant galaxies and the situation when the merger becomes problematic. We also define the region in the vicinity of our Local Group where the formation of the Hubble Flows starts.